Aplikasi Resep Kuliner Khas Indonesia Berbasis Flash - Kelvin Alexander Santoso; Liliana Liliana; Alexander Setiawan (Jurnal Infra, 2017)
the present time the existence of native culinary typical of Indonesia, many displaced by foreign culinary from abroad. This led to many young people today who are not familiar with Indonesian food, even the most severe, can not recognize the typical food of the area of origin of the person. Advances in technology is one of the main causes of the influx of foreigners into the country's culinary. This leads to the need for preservation of the unique culinary Indonesia back.This application will provide five menu of every province in Indonesia to be displayed to the user. Users can select a province, then the application will display five types of cuisine typical of the province. If the user selects a category before selecting a province, then the application will feature food from selected provinces in accordance with the categories that have been selected by the user. In this application there is also a search feature to search for food by name.Based on testing in Chapter 5, the design of existing applications is still not satisfactory for users. However, the information is displayed, according to the questionnaire results from five users could potentially use this application included either. Also users feel the ease of use of this application includes both. This application also according to a survey of five users is quite answer the needs.